2022
DOI: 10.1101/2022.03.18.22272607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-organ impairment and Long COVID: a 1-year prospective, longitudinal cohort study

Abstract: ImportanceMulti-organ impairment associated with Long COVID is a significant burden to individuals, populations and health systems, presenting challenges for diagnosis and care provision. Standardised assessment across multiple organs over time is lacking, particularly in non-hospitalised individuals.ObjectiveTo determine the prevalence of organ impairment in Long COVID patients at 6 and at 12 months after initial symptoms and to explore links to clinical presentation.DesignThis was a prospective, longitudinal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…One prospective study of low-risk individuals, looking at the heart, lungs, liver, kidneys, pancreas and spleen, noted that 70% of 201 patients had damage to at least one organ and 29% had multiorgan damage 69 . In a 1-year follow-up study, conducted by the same research group with 536 participants, the study authors found that 59% had single-organ damage and 27% multi-organ damage 70 . A dedicated kidney study of VA data including more than 89,000 individuals who had COVID-19 noted an increased risk of numerous adverse kidney outcomes 71 .…”
Section: Vascular Issues and Organ Damagementioning
confidence: 99%
“…One prospective study of low-risk individuals, looking at the heart, lungs, liver, kidneys, pancreas and spleen, noted that 70% of 201 patients had damage to at least one organ and 29% had multiorgan damage 69 . In a 1-year follow-up study, conducted by the same research group with 536 participants, the study authors found that 59% had single-organ damage and 27% multi-organ damage 70 . A dedicated kidney study of VA data including more than 89,000 individuals who had COVID-19 noted an increased risk of numerous adverse kidney outcomes 71 .…”
Section: Vascular Issues and Organ Damagementioning
confidence: 99%
“…A wide range of objective abnormalities have been reported in both Long COVID and ME/CFS. Multi-organ magnetic resonance imaging (MRI) imaging of many Long COVID patients and non-symptomatic post-COVID control subjects has revealed abnormalities involving many organs up to 1 year following acute COVID-19, although it is unclear if the anatomic MRI abnormalities reflect defective organ function: correlation of MRI abnormalities with persistent symptoms was poor (535).…”
Section: Comparison Of the Underlying Objective Biological Abnormalitiesmentioning
confidence: 99%
“…In addition, observational studies note that the cardiovascular sequalae of long COVID include chest pain, heart failure, dysrhythmias, cerebrovascular disorders, inflammatory heart disease, ischemic heart disease and thromboembolic disease (28,29). Further the adverse health outcomes in long COVID include the new onset of diseases, such as type 2 diabetes (30) and multi-organ damage (31). Given that a plethora of long COVID manifestations is not only observed in acute cases of COVID-19 but also significantly impact individuals with asymptomatic, mild or moderate initial SARS-CoV-2 infections that did not warrant hospitalization (7,32,33), severely exacerbates the health and socioeconomic burden of long COVID worldwide.…”
Section: Introductionunclassified